Problematizing the Minimum Age of Marriage: The State and Local Perspective on Marriage Dispensation in South Sulawesi - Nurul Ilmi Idrus (Humaniora, 2022)
Child marriage occurs throughout the world, in developed countries and especially in developing countries, including Indonesia. This article examines how categorisation of age is problematised particularly in relation to marriage dispensation after the amendments of marriage law in 2019. Using a qualitative approach, this study was conducted in Maros Baru District, Maros Regency, South Sulawesi. Thirty-seven participants were interviewed and a total of 30 participants were involved in three focus group discussions. Findings demonstrate that there is a gap between legal categorisation of age and its local interpretation in the context of marriage practices. While the amendment of marriage law in 2019 aims to increase the minimum age of marriage, marriage dispensation still occurs. Marriage dispensation is usually given under the consideration of supported evidence in relation to the benefits (maslahat) as well as the harms (mudharat). However, when a request of marriage dispensation is rejected, marriage still occurs. As such, it is common for unregistered marriage (nikah siri) to be a “way out”.